Public Perception of Civil Service Competence and Service Quality in Public Service Malls - Pantih, Suwardhi; Lagantondo, Herlan (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to analyze employee competence and its influence on service quality at the Central Sulawesi Public Service Mall. The population of this study is the community that uses the services of the Central Sulawesi Province Public Service Mall, while the sample of this study was determined using the accidental sampling technique. This technique is used with the consideration that the sample of this study is all people who come and use services at the Public Service Mall. This means that anyone who comes and is served will be used as a research sample. The data collection technique in this study uses observation and research questionnaires, while the data analysis of this study uses descriptive statistics and simple linear regression analysis. The results of this study indicate that employee competence has a significant effect on service quality at the Central Sulawesi Public Service Mall. This is indicated by the results of the regression test which confirms that competence has a real contribution to improving the quality of public services. Meanwhile, the results of descriptive statistics show that the knowledge dimension is the most dominant aspect of competence, while the trait dimension, especially the ability to deal with pressure, is still low. On the other hand, the highest service quality is seen in the assurance aspect, while the reliability dimension still needs to be improved, especially in relation to complaint resolution